Azolla biofertilizer growth and utilization for vegetable production - Widiastuti, Dwi P., author; Davis, Jessica G., advisor; Stromberger, Mary E., committee member; Bartolo, Michael E., committee member; Storteboom, Heather, committee member; Gafur, Sutarman, committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.
Keywords: peat; soil properties and plant nutrients; growth and yields; alluvial; soil microbial communities; Azolla